Evaluación del sistema de competencias genéricas y específicas de los estudiantes del quinto año nocturno, como efecto de la interacción académica, docente/alumno en la carrera de jurisprudencia de la Utmach, período lectivo 2015-2016 y propuesta de un plan de mejoras con énfasis en los estándares de calidad exigidos por el CEAACES. - Hurtado Gallegos, Angélica Elizabeth (2016)
The purpose of this study, tends to internalize the generic and specific competences of the graduate profile of the Jurisprudence Course, since most of the students are unaware of it, the majority of teachers indicate that they do not know the generic and specific competences of The Career of Jurisprudence, this deficiency significantly affects the professional practice, therefore not being acquired in the pedagogical process professionals are subject to make mistakes in writing and social interaction that put it in bad predicament which can lead to the Loss of prestige and the insecurity of working in the legal processes entrusted to them. Competences are the cornerstone of the Jurisprudence career, therefore it is the duty of teachers to develop them in all subjects as a cross-cutting axis as an effect of the pupil master relationship since there is no other way of transmitting them except through example.